El rol moderador de la capacidad de absorción en el desempe\~no innovador: Evidencia para el sector industrial de Argentina; The moderating role of absorption capacity on innovative performance: Evidence for the industrial sector of Argentina - Carolina Pasciaroni; Andrea Barbero (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– Knowledge from customers, suppliers, competitors, universities, is a key input in the innovative process of firms. However, firms must have absorption capacity to take advantage of such external knowledge. Based on the concept of absorptive capacity, this paper aims to analyze the impact that knowledge spillovers have on obtaining technological innovations by industrial firms located in Argentina and explore the moderating role that the absorption capacity exerts on such impact. Knowledge spillovers are one of the mechanisms or channels for access to external knowledge by firms. In this paper, such knowledge spillovers are captured through the concept of external sources of information. The external sources of information are differentiated into market, academic and general sources. After applying the Oaxaca-Blinder gap decomposition technique, no results are found in favor of a moderating effect of the absorption capacity for any of the external sources of information analyzed. Limitations, future directions, and policy implications are discussed.
Keywords: O31; O32; O33; 330; Innovation; knowledge spillovers; absorptive capacity; industry; Argentina